Chapter 9 Climate anxiety, fatalism and the capacity to act - Taylor, Dan (Taylor & Francis, 2023)
This chapter begins with the problem of 'climate anxiety', a psychological and cultural response to collapsing ecological systems marked by depression, trauma and helplessness. While a reasonable response to an existential threat, climate anxiety impedes our capacity to act where it leads to apathy, indecision or fatalism. The paper considers Jem Bendell's argument that accepting and 'grieving' for inevitable civilisational collapse is a precondition to clear-sighted adaptation. This response is insufficient for the problem of motivation necessary for the capacity to act. It considers Martha Nussbaum's 2018 claim that fear hinders reciprocity, amplifies infantile narcissism and endangers democracy. While salient, developing a countervailing 'capacity for concern' requires not merely a therapeutic relationship or the uncritical restitution of faltering liberal public institutions. Via Spinoza, an effective capacity to act against fear is conceived as interrelational and affective, founded on cooperation, friendship and the cultivation of causal knowledge. A common autonomy, one not merely of individual choice or identitarian self-expression.